Customer concentration, relationship, and debt contracting. Issue 2 (8th May 2017) - Yang, Ziyun
Abstract : Purpose: The purpose of this paper is to examine the effect of a firm's customer base concentration on its loan contract terms and how this effect varies with the strength of its customer relationship. Design/methodology/approach: This study is an archival research based on a sample of US public firms that have loan contract data between 1990 and 2008. Major customer sales data are used to construct customer concentration and customer relationship measures. A debt contract model is employed to relate loan spread and other contract terms to customer concentration and relationship. Findings: This study finds that firms with more concentrated customer bases have higher loan spread and shorter loan maturity and are more likely to issue secured loans. These negative effects disappear when the supplier firm maintains strong relationship with its customers. Research limitations/implications: Additional forward-looking measure of customer relationship could benefit future research. Practical implications: A firm's customer base characteristics can have significant impacts on the terms of its loan contracts. Findings from this study support the notion that customer relationship is an important intangible asset that is informative to stakeholders of the firm. Originality/value: This study proposes a new measure of customer relationship based on the past repeated relationships between a firm and its major customers. It shows that customer characteristics may affect firms' contracts with creditors: customer base concentration increases credit risk whereas strong customer relationship improves credit quality.